A systematic reclassification of Type IIn supernovae. Issue 4 (8th July 2021) - Ransome, C L; Habergham-Mawson, S M; Darnley, M J; James, P A; Filippenko, A V; Schlegel, E M
ABSTRACT: Type IIn supernovae (SNe IIn) are a relatively infrequently observed subclass of SNe whose photometric and spectroscopic properties are varied. A common thread among SNe IIn is the complex multiple-component hydrogen Balmer lines. Owing to the heterogeneity of SNe IIn, online data bases contain some outdated, erroneous, or even contradictory classifications. SN IIn classification is further complicated by SN 'impostors' and contamination from underlying H ii regions. We have compiled a catalogue of systematically classified nearby (redshift z < 0.02) SNe IIn using the Open Supernova Catalogue (OSC). We present spectral classifications for 115 objects previously classified as SNe IIn. Our classification is based on results obtained by fitting multiple Gaussians to the H α profiles. We compare classifications reported by the OSC and Transient Name Server (TNS) along with the best matched templates from snid . We find that 28 objects have been misclassified as SNe IIn. TNS and OSC can be unreliable; they disagree on the classifications of 51 of the objects and contain a number of erroneous classifications. Furthermore, OSC and TNS hold misclassifications for 34 and 12 (respectively) of the transients we classify as SNe IIn. In total, we classify 87 SNe IIn. We highlight the importance of ensuring that online data bases remain up to date when new or even contemporaneous data become available. Our work shows the great range of spectral properties and features that SNe IIn exhibit, which may be linked to multiple progenitor channels and environment diversity. We set out a classification scheme for SNe IIn based on the H α profile that is not greatly affected by the inhomogeneity of SNe IIn.